Complex optical elements for scanning helium microscopy through 3D printing. (26th November 2021) - Bergin, M; Myles, T A; Radić, A; Hatchwell, C J; Lambrick, S M; Ward, D J; Eder, S D; Fahy, A; Barr, M; Dastoor, P C
Abstract: Developing the next generation of scanning helium microscopes requires the fabrication of optical elements with complex internal geometries. We show that resin stereolithography (SLA) 3D printing produces low-cost components with the requisite convoluted structures whilst achieving the required vacuum properties, even without in situ baking. As a case study, a redesigned pinhole plate optical element of an existing scanning helium microscope was fabricated using SLA 3D printing. In comparison to the original machined component, the new optical element minimised the key sources of background signal, in particular multiple scattering and the secondary effusive beam.